2006
DOI: 10.1097/01.ta.0000174662.28239.f8
|View full text |Cite
|
Sign up to set email alerts
|

Motorcycle Collisions Involving White-Tailed Deer in Central and Northern Wisconsin: A Rural Trauma Center Experience

Abstract: DMC are a significant public health issue in mid-western states. Education about helmet and alcohol use and safety on rural roads may be the best prevention. Continued research focusing on prevention is necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 2 publications
1
3
1
Order By: Relevance
“…Unhelmeted riders were found to have a higher ISS compared to their helmeted counterparts. The mortality and injury pattern was substantial with 7 deaths along with a predominance of head, chest and orthopedic injuries [7]. This is in contrast to our review which found no such association between helmet use and injury severity.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…Unhelmeted riders were found to have a higher ISS compared to their helmeted counterparts. The mortality and injury pattern was substantial with 7 deaths along with a predominance of head, chest and orthopedic injuries [7]. This is in contrast to our review which found no such association between helmet use and injury severity.…”
Section: Discussioncontrasting
confidence: 76%
“…Pattern and severity of injury seems related to vehicle and animal size [5-7]. Abu-Zidan et al found Kangaroo-vehicle trauma in Australia resulted in a relatively mild pattern of injury with mostly head/face and extremity trauma.…”
Section: Discussionmentioning
confidence: 99%
“…Motorcyclists in northern states are more likely to ride their bikes in summer or spring as opposed to winter and fall because of the inclement weather. 6 As a consequence, given the cold winter in North Dakota, most of the collisions took place in summer or spring, similar to the study by Nelson et al 6 Most animal collisions happened at night; this observation is typically explained by the fact that deer and other large animals are moving around dusk and dawn, combined with relatively high traffic volume in the early morning and late afternoon. 1 Like previous investigations looking for risk factors associated with fatal AVCs, 2 ,3,7,8 most animal collisions happened in apparently ideal driving conditions, with clear weather, and on straight dry asphalt or concrete rural roads.…”
Section: Discussionsupporting
confidence: 54%
“…2,3 We were able to find only one study looking at the mortality of animal-motorcycle collisions. In the study by Nelson et al, 6 a retrospective chart review at a tertiary referral center in Wisconsin for a 9-year period (1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002), the authors identified 55 deer-motorcycle collisions in which 7 (12.7%) individuals died. This mortality rate, however, can be an overestimation if only the sickest patients were admitted and then referred to this tertiary medical center; additionally, this approach could underestimate the mortality because motorcycle drivers who died at the scene were not admitted.…”
Section: Discussionmentioning
confidence: 99%
“…Two-wheeled motorized vehicle crashes often involve multiple injuries that require extended hospital stay, 1 and are associated with disability and lost income. 2 In multiple states, there is a lack of regulatory restrictions for moped operation in particular. The lack of regulation provides a legal mode of transportation for operators who have had their driver's licenses rescinded for a variety of reasons, including previous driving while intoxicated or other criminal charges.…”
mentioning
confidence: 99%